Tittle Analisis Penyebab Meningkatnya Angka Perkara Cerai Gugat Tahun 2020-2022 di Pengadilan Agama Medan Kelas IA - Munthe, Masniari; Firmansyah, Heri (Fakultas Syariah INSURI Ponorogo, 2022)
Lately, it has been alleged that divorce cases in Indonesia have dominated divorce suits have been filed by the wives. Similar incidents were seen in Medan City, North Sumatra, by taking the Medan Religious Court Class I A sample. Data from the Medan Religious Court, the number of divorces reaches two thousand five hundred cases per year. If you look at the principles of the Marriage Law which complicate divorce, it seems contradictory, and even divorces continue to increase to this day. Against the background of the problems above, this study aims to determine the factors causing the increase in the number of divorce cases being sued in 2020-2022 at the Medan Religious Court. The author uses quantitative empirical legal research methods, namely procedures through data analysis based on statistics in the form of written and oral statements from the field. The conclusion of this study is that due to the weak family economy supported by social changes during the Covid-19 pandemic, many husbands are victims of mass layoffs, unable to meet family needs and are not responsible for supporting their families. wife and child. So there are always constant fights that lead to divorce. Then today's wives are more independent and understand their rights better as wives, access to information about divorce procedures is very easy to find through Google or LBH. So that the wife is certain to take steps to divorce her husband at the Medan Religious Court.